Das andere Chelsea - Eine Geschichte aus Donezk . The Other Chelsea – A Story from Donetsk - Preuss, Jakob (Kloos & Co. Medien GmbH, 2010)
Coproduction: Germany, Ukraine. Verzi FF These days, a real billionaire has to own a football team. Russian oligarch Roman Abramovich bought the English club Chelsea, Georgian Merab Jordania bought the Dutch Vitesse; and Ukrainian billionaire Rinat Akhmetov pumped millions into his hobby, Shakhtar Donetsk. This documentary is about two of the team’s fans: coal miner Sasha sits among the common people in the terraces, while local politician Kolya is proud to share the VIP box with the Ukrainian political and business elite. The billionaire Akhmetov invests heavily in the club, which is becoming a major European force during the season followed by the film. Yet this sporting success funded by an oligarch’s fortune only seems to highlight the wider social and political stagnation of the region. While following the ups and downs of Shakhtar, the director looks beyond soccer to where politics, showbiz and economics meet.